PENGARUH KEPEMILIKAN INSTITUSIONAL, DEWAN KOMISARIS, INTENSITAS PERSEDIAAN, DAN LEVERAGE TERHADAP MANAJEMEN PAJAK - Lia Lia puspita sari; Dwi Fitri Puspa (Jurnal Kajian Akuntansi dan Auditing, 2023)
The purpose of this research is to empirically examine the effect of institutional ownership, board of commissioners, inventory intensity, and leverage on tax management. This research was conducted at manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2017-2022. The sample selection was based on the purposive sampling method and in the end it was obtained 128 companies that met the criteria and the number of observations was 640 observations. The analysis technique used in this study is Multiple Linear Regression with the Eviews. The results show that institutional ownership, inventory intensity and leverage have a positive and significant effect on tax management, while the board of commissioners has no effect on tax management in manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2018-2022.